Axonal α7* nicotinic acetylcholine receptors modulate glutamatergic signaling and synaptic vesicle organization in ventral hippocampal projections - Zhong, Chongbo; Akmentin, Wendy; Role, Lorna W.; Talmage, David A. (Frontiers in Neural Circuits, 2022)
Modulation of the release of glutamate by activation of presynaptic nicotinic acetylcholine receptors (nAChRs) is one of the most prevalent mechanism of nicotinic facilitation of glutamatergic transmission in cortico-limbic circuits. By imaging gene chimeric co-cultures from mouse, we examined the role of α7* nAChRs mediated cholinergic modulation of glutamate release and synaptic vesicle organization in ventral hippocampal projections. We directly visualized exogenous and endogenous cholinergic facilitation of glutamate release in this specialized preparation of circuits in vitro. Disrupting α7* nAChRs mediated cholinergic signaling genetically or pharmacologically diminished cholinergic facilitation of glutamate release at presynaptic terminals. Alteration of α7* nAChRs mediated cholinergic signaling along glutamatergic axons also decreased functional synaptic vesicle clustering and vesicular trafficking to presynaptic terminals. These findings suggest that presynaptic α7* nAChRs contribute to cholinergic modulation of glutamate release and synaptic vesicle organization.